PERENCANAAN USAHA SEBAGAI PENENTU TINGKAT KEBERHASILAN USAHA BUMDESA BHAKTI JAYA SEDAYULAWAS KABUPATEN LAMONGAN - Agus Wahid Suyoto (Adpertens: Jurnal Ekonomi dan Manajemen, 2025)
This study analyzes the relationship between business planning and the success level of the Village-Owned Enterprises (BUMDesa) Bhakti Jaya Sedayulawas in Lamongan Regency, which plays a strategic role in village economic development. Although BUMDesa has significant potential, the implementation of planning functions that are not yet optimal often becomes an obstacle to achieving success. The research aims to explore the impact of business planning on BUMDesa's success. Using a descriptive quantitative method with purposive sampling on the Bolen bread business unit, data were collected through documentation and observation. The business planning variable was measured using the cost structure from the business model canvas, while success was assessed through the Break Even Point (BEP) and feasibility analysis. Pearson correlation analysis revealed a significance value of 0.000 (< 0.05) and a calculated r value of 0.912 (> r table 0.404), indicating a positive and significant correlation between business planning and success. The T-test further confirmed that the calculated t value (25.518) exceeds the t table value (1.71714), leading to the rejection of the null hypothesis. These findings suggest that effective business planning significantly enhances BUMDesa's success and recommend improvements in planning quality for optimal results.